Cladistic analysis of Landrevinae Gorochov, 1982 (Orthoptera, Gryllidae) - Redü, Darlan Rutz (2020)
The subfamily Landrevinae Gorochov, 1982 (sensu OSF) currently includes 194 valid species, distributed in 40 genera and three tribes. The tribe Landrevini comprises 28 genera and 160 species, almost all the subfamily, while Odontogryllini comprises five genera and 20 species, and Prolandrevini has seven genera and 14 species. This subfamily is a diverse group of forest crickets distributed specially in tropical clime of the Neotropical, Afrotropical, Oriental and Australasian biogeographic regions. A cladistic analysis is presented including 48 terminals and 106 morphological characters. The phylogenetic analysis with equal weight resulted in 14 most parsimonious trees, with 483 steps. The subfamily Landrevinae was recovered as a monophyletic clade, as well as Landrivini. Odontogryllini was recovered as a paraphyletic group, with Prolandrevini nested inside. This work is the first step towards an improvement in understand this complex group of crickets